Prilaku Ibu Hamil Pemanfaatan Desa Siaga di Hilisilawa Kec. Fanayama Kab. Nias Selatan Tahun 2023 - Fitri Muliani Kristina Gulo; Lisdayanti Simanjuntak; Juliana Munthe; Ribur Sinaga; Dina Afriani (Lembaga Pengembangan Kinerja Dosen, 2025)
Based on data from the World Health Organization (WHO), around 810 women die from pregnancy or childbirth complications worldwide every day. In 2021, it was recorded that 42,295 villages and sub-districts (56.1%) of the 75,410 villages and sub-districts in Indonesia had begun efforts to realize this Alert Village/Sub-district. Based on the results of a preliminary survey conducted in February, in Hilisalawa Village, Fanamaya District, South Nias Regency, out of 10 pregnant women, 6 pregnant women did not utilize the alert village. The data collection method was carried out by collecting primary data, namely by conducting direct interviews with respondents and providing questionnaires that were previously informed of how to fill out the questionnaire and collected back for processing. Of the 35 respondents, based on behavior, the majority behaved well as many as 22 people (63%) and the minority behaved poorly as many as 2 respondents (6%). Good behavior is due to a response received by someone from external stimuli, then creating an activity or activity in utilizing the Alert Village